Welfare Leavers' Use of Medicaid Transitional Medical Assistance in California, 1993-1997 - Jane Mauldon; Kamran Nayeri; Carlos Dobkin (SAGE Publishing, 2002)
Using administrative and survey data, we estimate participation rates in Transitional Medical Assistance (TMA) for the period 1993-97 by California welfare leavers during their first six months post-welfare. We find that although many welfare leavers were eligible for TMA (35% to 47% of exiters), only 26% of eligible people were enrolled in the TMA program. Another 14% were covered by non-TMA Medicaid for the entire six months. Most TMA-eligible exiters had Medicaid coverage (all of it non-TMA) for less than six months (49%) or no Medicaid coverage at all (11%). Supplementary analyses using data from the National Survey of America's Families indicate that if fully implemented, TMA could have substantially reduced uninsurance among welfare leavers.